Analysis of Community Participation Level in the Community Empowerment Program of Gold Mining Company - Ni Made Ayu Wina Wirjana Asak; Budi Santosa (Journal of Social Research, 2024)
Mining companies play an important role in creating sustainable communities around their operational areas. PT ANTAM Tbk UBP Emas (ANTAM UBP Emas), located in Bantar Karet Village, Nanggung District, Bogor Regency, focuses on the exploration of mineral resources, particularly gold and silver. The surrounding community generally works in the agriculture, plantation, home industry, and fishery sectors. This study aims to analyze: (i) community empowerment program activities run by the company, (ii) the level of community participation in empowerment program planning, (iii) the level of community participation in program implementation, (iv) the level of community participation in the utilization of program results, and (v) the level of community participation in empowerment program evaluation. The research design used is qualitative research with descriptive analysis method. The results showed that the level of community participation in the empowerment program which includes the stages of planning, implementation, utilization of results, and evaluation still needs to be improved. ANTAM UBP Emas needs to evaluate mentoring methods, implement training programs, and capacity building for group members as an effort to accelerate the increase in participation to achieve the level of Citizen Power participation, so that this program can become a means of corporate exit strategy in accordance with the needs and context of the community.